Video Game Data Synchronization and Preservation using Blockchain - Kristoforus Adi Agung; Cutifa Safitri; Andika Candra Jaya; Rinaldi Aditya Pratama; A.M. Hermanto Laksana; Hasanul Fahmi (SEAN Institute, 2023)
As live-service games proliferate, game availability starts to concern player due to the need to fund the game servers. Game companies had been known to remove games at will, frequently for financial reasons. Players and others are scrambling to figure out how to preserve games and make it available offline. Our goal is to allow synchronization and preservation of game data. We propose using blockchain technology and we are building a game as proof of concept of this proposal. We found that we could preserve and allow synchronization of game data to our blockchain that could be maintained among several players.